Teaching communication behaviour through dance and movement to children with Autism Spectrum Disorder (ASD) in Sarawak / Teo Jing Xin...[et al.] - Teo, Jing Xin; Lau, Bee Theng; Patrick, Then (2019)
This paper highlights the struggles of parents in Sarawak that have children with autism spectrum disorders (ASD), and introduces the authors’ proposed intervention programme for this population. With the belief that parental buy-in to an intervention would result in a higher level of follow-through and therefore improvement to the benefit of their children, the Fun, Inclusive, and Tolerant (FIT) dance and movement based behavioural intervention was designed and developed for Sarawakian children on the spectrum, specifically with the objective to acknowledge and address parental cultural narratives, desires, and expectations; while teaching appropriate behaviours to their children. The focus of this paper is two-fold. Firstly, to demonstrate how dances in this programme were created, by explaining the formulation of an individual dance which was developed for a child with an expressive speech delay; and secondly, to present parental feedback regarding the programme. Concluding remarks touch upon the authors’ future directions in this research.